Prediction of particle level behavior in atmospheric air based on laws of physics of motion and geographic interpolation. (December 2020) - Carrillo, G; Carrillo, G E
Abstract: Given the global problem of high levels of pollutants in the atmosphere, it is essential to use tools to measure and determine these levels. Unfortunately, it is impossible to have devices that allow direct pollutants' direct measurements in a place of interest. Due to this limitation, in this work, a computer tool was developed to predict contaminants' behavior and their concentration levels in a reliable way. In this methodology, equations of the physics of motion were implemented to predict particles' behavior in a given area and an interpolation technique based on the Kriging method. In the initial stage, a preliminary analysis of the pollution data of the city of Bogota, Colombia, downloaded from the Air quality monitoring network of Bogota, Colombia, was performed. In the next stage, the variables of most significant interest in the analysis were defined, and the data to be characterized is explored. Finally, the selected method's calculation algorithm is implemented in Python, taking an ArcGIS library as a programming reference. From the results, it was possible to determine the contaminants' levels for some regions of Bogota, Colombia, between values of 0.067 to a maximum weight of 0.4039 ¼g/m 3, for January 2013.